Improvement Of Control System On Programmable-Based DC Excitation Generator Logic Controller - Zepri Irwansyah; Solly Aryza; Adi Sastra Tarigan (INFOKUM, 2021)
A direct current generator is an electrical system that converts mechanical energy into electrical energy dynamically. An independent and separate excitation type DC gener-ator is a field generator that can be connected to a DC source independently of the en-gine. When a DC voltage is introduced into the field coil in the form of resistance Rf, a current If is generated and flux is created at both poles. In this study discusses a new control system in a generator that is given a load, the generator output voltage is re-duced. The so-called mechanism in regulating the excitation voltage to control the out-put voltage. When the generator is equipped with a PLC operating at the same field voltage, the induced voltage is greater; for example when the voltage is 14.01 Volts or 15.41 Volts, the induced voltage is 34,311 Volts or 51,587 Volts.